Microsegregation of peritectic systems in a temperature gradient: Analysis in directionally solidified Sn–36at.%Ni peritectic alloy. (March 2016) - Peng, Peng; Li, Xinzhong; Su, Yanqing; Guo, Jingjie; Fu, Hengzhi
Highlights: Effect of the TGZM effect on microsegregation is predicted. Effect of peritectic reaction on microsegregation is predicted. Both solid solution phase and intermetallic phases are taken into consideration. Abstract: Microsegregation is influenced by many factors during solicitation while the coupling effects of some important factors have been dismissed. During directional solidification of Sn–36at.%Ni peritectic alloys under high temperature gradient, melting/solidification of both the primary and peritectic phase caused by temperature gradient zone melting has been observed. An analytical model has been proposed to analyze the effect of temperature gradient zone melting on microsegregation of interdendritic melt in peritectic alloys. The coupling influences of peritectic reaction, coarsening process and solid state back-diffusion have all been included in this model. Both the experimental and theoretical analyses have demonstrated that melting/solidification of both the primary and peritectic phase could be accelerated by temperature gradient zone melting during peritectic solidification. Thus, microsegregation of interdendritic melt is restricted by temperature gradient zone melting during peritectic solidification. The analytical model in the present work shows inherent consistence with our previous models.